Seasonal Variation in Vitamin D3 Levels Is Paralleled by Changes in the Peripheral Blood Human T Cell Compartment - Khoo, Ai-Leng; Koenen, Hans J. P. M.; Chai, Louis Y. A.; Sweep, Fred C. G. J.; Netea, Mihai G.; van der Ven, André J. A. M.; Joosten, Irma (PLOS ONE, 2012)
It is well-recognized that vitamin D3 has immune-modulatory properties and that the variation in ultraviolet (UV) exposure affects vitamin D3 status. Here, we investigated if and to what extent seasonality of vitamin D3 levels are associated with changes in T cell numbers and phenotypes. Every three months during the course of the entire year, human PBMC and whole blood from 15 healthy subjects were sampled and analyzed using flow cytometry. We observed that elevated serum 25(OH)D3 and 1,25(OH)2D3 levels in summer were associated with a higher number of peripheral CD4+ and CD8+ T cells. In addition, an increase in naïve CD4+CD45RA+ T cells with a reciprocal drop in memory CD4+CD45RO+ T cells was observed. The increase in CD4+CD45RA+ T cell count was a result of heightened proliferative capacity rather than recent thymic emigration of T cells. The percentage of Treg dropped in summer, but not the absolute Treg numbers. Notably, in the Treg population, the levels of forkhead box protein 3 (Foxp3) expression were increased in summer. Skin, gut and lymphoid tissue homing potential was increased during summer as well, exemplified by increased CCR4, CCR6, CLA, CCR9 and CCR7 levels. Also, in summer, CD4+ and CD8+ T cells revealed a reduced capacity to produce pro-inflammatory cytokines. In conclusion, seasonal variation in vitamin D3 status in vivo throughout the year is associated with changes in the human peripheral T cell compartment and may as such explain some of the seasonal variation in immune status which has been observed previously. Given that the current observations are limited to healthy adult males, larger population-based studies would be useful to validate these findings.